Connectivity Indices of Power Graphs over Dihedral Groups of a Certain Order - Munandar, Arif (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2025)
The dihedral group is a mathematical structure generated by rotational and reflection symmetries. In this study, the representation of the group is described using a power graph, where all elements of the group are treated as vertices, and two distinct elements are considered adjacent when one is a power of the other. By analyzing the structural patterns of the resulting power graphs, various connectivity indices can be determined, particularly for dihedral groups whose orders are powers of a prime number. This research focuses on six specific connectivity indices: the first Zagreb index, the second Zagreb index, the Wiener index, the hyper-Wiener index, the Harary index, and the Szeged index.